US Monetary Policy in a Globalized World - Jesús Crespo Cuaresma; Gernot Doppelhofer; Martin Feldkircher; Florian Huber (Oesterreichische Nationalbank (OeNB), 2016)
We analyze the interaction between monetary policy in the US and the global economy proposing a new class of Bayesian global vector autoregressive models that accounts for time-varying parameters and stochastic volatility (TVP-SV-GVAR). We find that a contractionary US monetary policy shock leads to a persistent fall in international output, a drop in global inflation rates, a rise in international interest rates and a strengthening of the US dollar in real terms. There is considerable evidence for heterogeneity of spillovers across countries, as well as for changes in the transmission of monetary policy shocks over time. We also examine the reverse question, namely how US monetary policy responds to international shocks. Here we find that US short-term rates decrease significantly in response to a monetary policy tightening abroad or a negative shock to foreign real GDP growth.
Keywords: C18; C26; E21; 330; Global vector autoregression; time-varying parameters; stochastic volatility; monetary policy; international spillovers; Geldpolitik; Geldpolitische Transmission; USA; Schock; Spillover-Effekt; Stochastische Volatilität; VAR-Modell; Welt